Cardiopulmonary exercise test and sudden cardiac death risk in hypertrophic cardiomyopathy. Issue 8 (5th February 2016) - Magrì, Damiano; Limongelli, Giuseppe; Re, Federica; Agostoni, Piergiuseppe; Zachara, Elisabetta; Correale, Michele; Mastromarino, Vittoria; Santolamazza, Caterina; Casenghi, Matteo; Pacileo, Giuseppe; Valente, Fabio; Musumeci, Beatrice; et al.
Abstract : Background: In hypertrophic cardiomyopathy (HCM), most of the factors associated with the risk of sudden cardiac death (SCD) are also involved in the pathophysiology of exercise limitation. The present multicentre study investigated possible ability of cardiopulmonary exercise test in improving contemporary strategies for SCD risk stratification. Methods: A total of 623 consecutive outpatients with HCM, from five tertiary Italian HCM centres, were recruited and prospectively followed, between September 2007 and April 2015. The study composite end point was SCD, aborted SCD and appropriate implantable cardioverter defibrillator (ICD) interventions. Results: During a median follow-up of 3.7 years (25th–75th centile: 2.2–5.1 years), 25 patients reached the end point at 5 years (3 SCD, 4 aborted SCD, 18 appropriate ICD interventions). At multivariate analysis, ventilation versus carbon dioxide relation during exercise (VE/VCO2 slope) remains independently associated to the study end point either when challenged with the 2011 American College of Cardiology Foundation/American Heart Association guidelines-derived score (C index 0.748) or with the 2014 European Society of Cardiology guidelines-derived score (C index 0.750). A VE/VCO2 slope cut-off value of 31 showed the best accuracy in predicting the SCD end point within the entire HCM study cohort (sensitivity 64%, specificity 72%, area under the curve 0.72). Conclusions: Our data suggest that the VE/VCO2 slope might improve SCD risk stratification, particularly in those HCM categories classified at low-intermediate SCD risk according to contemporary guidelines. There is a need for further larger studies, possibly on independent cohorts, to confirm our preliminary findings.